Five decades of corporate entrepreneurship research: measuring and mapping the field - Maria Glinyanova; Ricarda B. Bouncken; Victor Tiberius; Antonio C. Cuenca Ballester (International Entrepreneurship and Management Journal, 2021)
Research on corporate entrepreneurship—venturing activities by established corporations—has received increasing scholarly attention. We employ bibliometric methods to analyze the literature on corporate entrepreneurship published over the last five decades. Based on the results of citation and co-citation analyses, we reveal central works in the field and how they are interconnected. We investigate the underlying intellectual structure of the field. Our findings provide evidence of the growing maturity and interdisciplinarity of corporate entrepreneurship and provide insight into research themes. We find that resource-based view and its extensions still remain the predominant theoretical perspectives in the field. Drawing on these findings, we suggest directions for future research.
Keywords: 650; Corporate entrepreneurship; Bibliometric analysis; Co-citation analysis